Matplotlib plotting cookbook : learn how to create professional scientific plots using matplotlib, with more than 60 recipes that cover common use cases /: learn how to create professional scientific plots using matplotlib, with more than 60 recipes that cover common use cases. (2014) - Unknown
No abstract available